Prognostic significance of white blood cell to platelet ratio in delayed cerebral ischemia and long-term clinical outcome after aneurysmal subarachnoid hemorrhage - Zhang, Wanwan; Wang, Yifei; Zhang, Qingqing; Hou, Fandi; Wang, Lintao; Zheng, Zhanqiang; Guo, Yong; Chen, Zhongcan; Hernesniemi, Juha; Feng, Guang; Gu, Jianjun (Frontiers in Neurology, 2023)
Objectives The ratio of white blood cell to platelet count (WPR) is considered a promising biomarker in some diseases. However, its prediction of delayed cerebral ischemia (DCI) and prognosis after aneurysmal subarachnoid hemorrhage (aSAH) has not been studied. The primary objective of this study was to investigate the predictive value of WPR in DCI after aSAH and its impact on 90-day functional outcome. Materials and methods This study retrospectively analyzed the data of blood biochemical parameters in 447 patients with aSAH at early admission. Univariate and multivariate analyses were used to determine the risk factors for DCI. According to multivariate analysis results, a nomogram for predicting DCI is developed and verified by R software. The influence of WPR on 90-day modified Rankin score (mRS) was also analyzed. Results Among 447 patients with aSAH, 117 (26.17%) developed DCI during hospitalization. Multivariate logistic regression analysis showed that WPR [OR = 1.236; 95%CI: 1.058–1.444; p = 0.007] was an independent risk factor for DCI. The receiver operating characteristic (ROC) curve analysis was used to evaluate the predictive ability of WPR for DCI, and the cut-off value of 5.26 (AUC 0.804, 95% CI: 0.757–0.851, p < 0.001). The ROC curve (AUC 0.875, 95% CI: 0.836–0.913, p < 0.001) and calibration curve (mean absolute error = 0.017) showed that the nomogram had a good predictive ability for the occurrence of DCI. Finally, we also found that high WPR levels at admission were closely associated with poor prognosis. Conclusion WPR level at admission is a novel serum marker for DCI and the poor prognosis after aSAH. A nomogram model containing early WPR will be of great value in predicting DCI after aSAH.